Transmission of infection among health care personnel performing surgical tracheostomies on COVID-19 patients. Issue 5 (October 2021) - Angamuthu, Natarajan; Geraldine Gagasa, Emelia; Baker, Daryll; Tsui, Janice; Evan D'Souza, Rovan
Abstract: Background: Staff and patient safety are of paramount importance while performing a surgical tracheostomy (ST) during the corona virus disease (COVID-19) pandemic. The aim was to assess the incidence of COVID-19 infection among the healthcare personnel (HCP) performing ST on COVID-19 patients. Methods: One hundred and twenty-two HCP participating in 71 ST procedures performed at our institution between 26th March 2020 and 27th May 2020 were identified. A COVID-19 health questionnaire was distributed among staff with their consent. Data related to the presence of COVID-19 symptoms (new onset continuous cough, fever, loss of taste and/or loss of smell) among HCP involved in ST as well as patient related data were collected. Results: Of the HCP who responded, eleven (15%, 11/72) reported key COVID-19 symptoms and went into self-isolation. Ten members from this group underwent a COVID-19 swab test and three tested positive. Only one HCP attended hospital for symptomatic treatment, none required hospitalisation. Sixty percent (43/72) of the responders had a COVID-19 antibody test with a positive rate of 18.6% (8/43). Among the patients undergoing a ST, 67% (37/55) required a direct intensive care unit (ICU) admission; the mean age was 58 years (29–78) with a male preponderance (65.5%). The median time from intubation to ST was 15 days (range 5–33, IQR = 9). The overall mortality was 11% (6/55). Conclusions: ST can be carried out safely with strict adherence to both, personnel protective equipment and ST protocols which are vital to mitigate the potential transmission of COVID-19 to the HCP. Graphical abstract: Image 1 Highlights: - Tracheostomy in COVID-19 patients puts healthcare staff at risk of the infection. - Adherence to tracheostomy protocol is essential to minimise aerosol contamination. - Personal protective equipment helps in mitigating cross infection among healthcare personnel.